Low self-reported penicillin allergy in South Africa—implications for global public health response. Issue 1 (21st February 2023) - Day, Cascia; Mendelson, Marc; Peter, Jonny; ,
Abstract: Objectives: In high-income countries, up to 25% of inpatients have a self-reported penicillin allergy (PA). After testing, 95% of these self-reported PAs are incorrect. These incorrectly labelled PAs increase the use of broad-spectrum antibiotics, and drive bacterial resistance. The epidemiology of PA in low- and middle-income countries is unknown. We aimed to describe the epidemiology and delabelling outcomes of self-reported PA in South African (SA) inpatients. Methods: We conducted point prevalence surveys between April 2019 and June 2021 at seven hospitals in Cape Town, South Africa. A team trained in the PEN-FAST allergy decision tool conducted in-person interviews, and reviewed patient notes to identify and risk stratify inpatients with a self-reported PA. These patients were referred to the Groote Schuur Hospital (GSH) allergy clinic for delabelling. Results: A total of 1486 hospital inpatients were surveyed and 3.2% ( n  = 48) carried a PA label. Importantly, 64.6% ( n  = 31) were classified by PEN-FAST as low risk for true penicillin hypersensitivity. Overall, 25% of the self-reported PAs received a β-lactam antibiotic in hospital and were directly delabelled. Delabelling attrition was very high, with 6.3% (3/48) of the self-reported PAs attending the GSH allergy clinic, and only one patient proceeding to a negative oral penicillin challenge. Conclusions: Inpatient self-reported PA was lower in South Africa hospitals compared with other upper-middle-income countries, and the majority of patients carried a low-risk PA label. Linkage for delabelling with the allergy clinic was very poor, and thus strategies to improve access and delivery of delabelling remains an urgent public health issue.